Analysis of Science Process Skills to Application of Module Practicum Ethno-STEM for Senior High School - Utrujjah, Fauziah; Hartono, Hartono; Wahyuni, Siti (Physics Communication, 2024)
Science process skills are essential for 21st century learning. The science process skills of senior high school students in many cities are still relatively low. The purpose of the research is to analyze science process skills that involve the environment or culture around students as a learning medium using the Ethno-STEM practicum module. The method used was quasi-experimental with a one-group pretest-posttest design. The research subjects were selected from Islamic Senior High School 2 Semarang, totaling 108 students. The sampling technique employed was purposive sampling. Data collection was in the form of observation, science process skills, and posttest. Data analysis used a validity test, reliability test, and N-gain test. The research results show an analysis of each indicator of science process skills for each practicum, and there is an increase in learning outcomes. Evidenced analysis of the results of each indicator of science process skills obtained 70.29% (observation), 58.49% (interpretation), 53.86% (hypothesizing), 75.62% (experimentation), 75.15% (collaboration), and 62.50% communication. Meanwhile, the results of studying the N-Gain test, which obtained a value of 0.7 in the high category.